Conceptions of health for users and professionals of a family health strategy - Maria de Lourdes Denardin Budó; Maria Denise Schimith; Raquel Pötter Garcia; Margot Agathe Seiffert; Bruna Sodré Simon; Fernanda Machado da Silva (Universidade Federal de Santa Maria, 2014)
Doi: 10.5902/2179769210461 Aims: to identify the conceptions of health of users and health professionals of a Family Health Strategy located in a city of the south of Brazil. Methods: descriptive and qualitative study realized with key informants: six residents, six community health agents and seven other members of the family health team. For the data collection the Participatory Rapid Appraisal was used, with the observation and interview as data sources. A theme analysis was carrierd out with the data. Results: health was pointed out by the key informants as a condition for life maintenance, as a result of the interaction of various aspects, conditions and lifestyle, influenced by occupation and social interactions. Conclusions: the professionals should involve social, environmental and psychological aspects in the planning of the assistance, since these significantly appeared to be determining in regards to health.